Gene expression in the Gitr locus is regulated by NF-κB and Foxp3 through an enhancer. - Tone, Y; Kidani, Y; Ogawa, C; Yamamoto, K; Tsuda, M; Peter, C; Waldmann, H; Tone, M (American Association of Immunologists, 2014)
Glucocorticoid-induced TNFR (Gitr) and Ox40, two members of the TNFR superfamily, play important roles in regulating activities of effector and regulatory T cells (Treg). Their gene expression is induced by T cell activation and further upregulated in Foxp3+ Treg. Although the role of Foxp3 as a transcriptional repressor in Treg is well established, the mechanisms underlying Foxp3-mediated transcriptional upregulation remain poorly understood. This transcription factor seems to upregulate expression not only of Gitr and Ox40, but also other genes, including Ctla4, Il35, Cd25, all critical to Treg function. To investigate how Foxp3 achieves such upregulation, we analyzed its activity on Gitr and Ox40 genes located within a 15.1-kb region. We identified an enhancer located downstream of the Gitr gene, and both Gitr and Ox40 promoter activities were shown to be upregulated by the NF-κB-mediated enhancer activity. We also show, using the Gitr promoter, that the enhancer activity was further upregulated in conjunction with Foxp3. Foxp3 appears to stabilize NF-κB p50 binding by anchoring it to the enhancer, thereby enabling local accumulation of transcriptional complexes containing other members of the NF-κB and IκB families. These findings may explain how Foxp3 can activate expression of certain genes while suppressing others.